Toward country-led development : a multi-partner evaluation of the comprehensive development framework - The International Bank for Reconstruction and Development; The World Bank. (Washington, D.C. : World Bank, 2003)
This evaluation, conducted by multi-disciplinary teams with members from developed and developing countries, shows that both donors and recipients have made progress in implementing the CDF principles, particularly in countries where one or more of the principles have been applied over a number of years. However, these positive changes are fragile and could be stalled or reversed. Implementing the principles requires changes in entrenched behaviours and institutional practices. Thus, dedicated and consistent attention is needed by top donor leadership and recipient countries to ensure that momentum is sustained.
Includes bibliographical references: p. 129-132.
gau 31/10/2016
Loans
Keywords: Economic assistance